2017
DOI: 10.1007/s12520-017-0499-0
|View full text |Cite
|
Sign up to set email alerts
|

Timber exploitation during the 5th–3rd millennia BCE at Arslantepe (Malatya, Turkey): environmental constraints and cultural choices

Abstract: A considerable amount of charcoal remains from the archaeological site of Arslantepe (Eastern Anatolia) has been analysed. The anthracological assemblage comes from seven archaeological periods, ranging from the Late Chalcolithic 1–2 (mid-5th millennium BCE) to the Early Bronze Age III (late 3rd millennium BCE). The woody taxa exploited by the local communities appeared to have only mi- nor changes throughout the investigated periods. For the eval- uation of wood use practices, charcoal was chronologically gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…The archaeobotanical research at Arslantepe has been carried out for more than 35 years. Several studies have focused on charcoal remains . Architectural woods were abundant since roof structures, and sometimes walls, were made of beams and smaller sticks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The archaeobotanical research at Arslantepe has been carried out for more than 35 years. Several studies have focused on charcoal remains . Architectural woods were abundant since roof structures, and sometimes walls, were made of beams and smaller sticks.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, some of the buildings were supplied with hearths, ovens and other domestic features, in which wood remains were preserved by charring. Archaeobotanical analysis especially revealed that the wood resources were exploited from two main vegetation zones: the plain, where deciduous oaks probably grew, and the surrounding mountain and hill slopes, where juniper trees were available …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…et al, 2020;Kennett et al, 2020). As a source of energy and raw material for production, wood is an essential resource in daily life and has played a critical role in human environmental adaptation throughout history (Martín-Seijo et al, 2015;Medina-Alcaide et al, 2015;Masi et al, 2017;Kabukcu, 2018;Liu et al, 2019a,b). Prehistoric humans usually collected locally available wood resources, following the "principle of least effort" (Renfrew and Bahn, 1991;Shackleton and Prins, 1992;Qing et al, 2010;Masi et al, 2017;Bouchaud et al, 2020).…”
Section: Introductionmentioning
confidence: 99%